Patient Perspectives on a Rapid Access, Walk-in, Medication for Addiction Treatment Clinic - Peng L; Bormann NL; Arndt S; Miskle BA; Weber AN (Substance Abuse and Rehabilitation)
Linda Peng,1 Nicholas L Bormann,2 Stephan Arndt,3,4 Benjamin A Miskle,3,5 Andrea N Weber3,6 1Carver College of Medicine, University of Iowa, Iowa City, IA, USA; 2Department of Psychiatry and Psychology, Mayo Clinic, Rochester, MN, USA; 3Department of Psychiatry, University of Iowa, Iowa City, IA, USA; 4Department of Biostatistics, University of Iowa, Iowa City, IA, USA; 5College of Pharmacy, University of Iowa, Iowa City, IA, USA; 6Department of Internal Medicine, University of Iowa, Iowa City, IA, USACorrespondence: Linda Peng, Carver College of Medicine, University of Iowa, 375 Newton Road, Iowa City, IA, 52242, USA, Tel +1 319-335-6707, Email linda-peng@uiowa.eduPurpose: Rapid access addiction medicine (RAAM) walk-in clinics offer low-barrier, prompt treatment for substance use disorders (SUDs). These models differ from bridge clinics, which primarily address the barriers of transitioning between inpatient and outpatient SUD treatment settings. Previous RAAM models have been shown to be effective in urban areas. Through patient interviews, this qualitative study sought to describe the unique challenges and successes of a RAAM clinic that serves a primarily rural area.Patients and Methods: Adult patients with a SUD who utilized a medication for addiction treatment (MAT) walk-in clinic participated in semi-structured, recorded interviews. Participants were asked about facilitators and barriers to attaining treatment, as well as their perspectives/experiences and unmet wants/needs. Interviewee responses were transcribed, qualitatively coded, and analyzed for prominent trends.Results: Twelve patients participated. Stigma, lack of rural treatment options, and accessibility concerns were identified as general barriers to receiving SUD care. MAT walk-in clinic specific barriers included distance to clinic, clinic hours, and transportation. Patients identified the clinic’s walk-in structure as a primary facilitator of receiving quality SUD care and felt the clinic offered a non-judgmental and accessible environment, differing positively from past treatments. Unmet wants and needs that patients identified included more extensive social services and communication after leaving the clinic.Conclusion: This MAT walk-in clinic is the only RAAM-style clinic offering same-day dual-diagnosis medication management in the state of Iowa. The walk-in structure was a key facilitator for patients accessing initial care. Expanding RAAM models in rural areas and incorporating telehealth may help address proximity barriers reported by patients.Keywords: substance use disorders, qualitative evaluation, rural health